Effects of screw-pressing temperature on the functional properties and structural characteristics of apricot (Prunus armeniaca L.) kernel protein isolates - Zhang, Li; Wu, Hongyu; Wang, Mengshi; Zhou, Xianjin; Bayinkexike,; Cui, Ruiguo; Song, Lijun; Liu, Fengjuan (Frontiers in Nutrition, 2025)
This study aimed to investigate the effect of screw-pressing temperature on the quality of apricot kernel protein isolates (API). The API values at different screw-pressing temperatures (40–200°C) were obtained, and the functional and structural properties of different API samples were comparatively studied. The results revealed that the total polyphenol content (TPC), total flavonoid content (TFC), and antioxidant activities (DPPH and FRAP assays) increased significantly with increasing temperature. High-temperature pressing also increased the surface hydrophobicity and emulsification of API. SDS-PAGE confirmed the preservation of the primary structure of API, with molecular weights ranging from 13 to 20 kDa and 36–56 kDa. Circular dichroism (CD) spectroscopy analysis revealed that the α-helix content increased (by 4–8%) and the β-sheet content decreased (by 2–5%) when the samples were pressed at high temperatures. The decrease in fluorescence intensity and the fluorescence spectral shift indicated changes in the tertiary structure. Multivariate statistical analysis revealed that the antioxidant activities were positively correlated to protein carbonyls, free sulfhydryl groups, surface hydrophobicity, TPC, and TFC. Mechanistically, thermally-induced protein conformational changes and surface hydrophobicity modulation drove the observed enhancements in functional properties. These findings will collectively serve as a theoretical basis for the efficient preparation and application of API.